Audience Interpretation of Humor Style on Redaksiana Crime News - Maulana Khalidin .; Triyono Lukmantoro .; Taufik Suprihartini .; Turnomo Rahardjo . (Interaksi Online, 2016)
Until now, television in Indonesia is still become primary mass media for audience. They make television as an information resources, entertainment, education, and reflection of our society for social control. Humor has became main part of entertainment on our television since a long time ago. Almost all of the television stations has made humor program, and Redaksiana is one of them. A program that broadcasted by Trans 7 is a news crime which is interspersed with humor. But, humor element that used by Redaksiana exploits a group in our society. So, this research aims to know about audience interpretation of humor style on Redaksiana. This research was a descirptive type of research with qualitative. The subjects are five informant with different social and culture.This study used preferred reading theory by Stuart Hall. In reception analysis, the findings research that derived from interview would raised three main types of interpretation. That findings research is there are two informants who performs dominant hegemonic reading that interpreted Redaksiana as an entertainment and informative program. The oppositional reading consist of one person has made critical interpretation that Redaksiana is not entertaining, informative and has exploited the lower classes. Meanwhile, negotiated reading group has two informants has made two side of interpretation, that is lower classes exploitation is awful action. But, they assume that is fair because media institutions is profit oriented. So, they tend to do hegemonic and negotiated reading. The study of humor style interpretation on Redaksiana news can be made as a foundation for the next researches and study in active audience field adds study about preferred rading theory.